Role of phospholipase A(2) and tyrosine kinase in Clostridium difficile toxin A-induced disruption of epithelial integrity, histologic inflammatory damage and intestinal secretion - Lima, Aldo A. M.; Nascimento, Nilberto R. F.; Fang, Guodong D.; Yotseff, Peter; Toyama, M. H. [UNESP]; Guerrant, Richard L.; Fonteles, Manasses C. (John Wiley & Sons Ltd, 2008)
Clostridium difficile-associated disease causes diarrhea to fulminant colitis and death. We investigated the role of phospholipase A(2) (PLA(2)) inhibitors, aristolochic acid (AA), bromophenacyl bromide BPB and quinacrine (QUIN) on the C. difficile toxin A-induced disruption of epithelial integrity, histologic inflammatory damage and intestinal secretion. Toxin A caused severe hemorrhagic and inflammatory fluid secretion at 6-8 h in rabbit ileal segments, an effect that was significantly inhibited by QUIN (71%, P < 0.01), AA (87%, P < 0.0001) or by BPB (51%, P < 0.01). The secretory effect of toxin A was also inhibited in segments adjacent to those with AA (89%, P < 0.01). Furthermore, QUIN or AA substantially reduced the histologic damage seen after 6-8 h in rabbit ileal segments. The cyclooxygenase inhibitor, indomethacin, also significantly inhibited (96%; n = 6) the secretory effects of toxin A in ligated rabbit intestinal segments. The destruction by toxin A of F-actin at the light junctions of T-84 cell monolayers was not inhibited by AA or BPB. AA or QUIN had no effect on the T-84 cell tissue resistance reduction over 8-24 h after toxin A exposure. All the inhibitors were shown to be effective in the doses administered direct in ileal loops to inhibit PLA(2) activity. The data suggest that PLA(2) is involved in the major pathway of toxin A-induced histologic inflammatory damage and hemorrhagic fluid secretion. Cop. right (C) 2008 John Wiley & Sons, Ltd.
Keywords: PLA(2); toxin A enterotoxin; C. difficile; PLA(2) inhibitors; diarrhea; GTPases; F-actin; tight junctions; cytoskeleton disruption; erbstatin